Hubungan Kecemasan Dan Aktivitas Fisik Dengan Gangguan Tidur Ibu Hamil TM III Di Rs.Ummi Bengkulu Tahun 2024 - Elviyanti, Desi; Sulastri, Mepi; Saputri, Meita Tria (Utami Publisher, 2024)
The prevalence of pregnant women in Asia is estimated to be 48.2% Africa 57.1% and Europe 25.1%. (WHO, 2020). Based on data from the National Sleep Foundation, the number of third trimester pregnant women who always wake up at night is 97.3%, an average of 3-11 times every night. the number of pregnant women in America who experience sleep disorders is 78% and only 1.9% of pregnant women who do not wake up at night during third trimester pregnancy. Based on an initial survey conducted on March 04, 2024 on TM III mothers in Ummi Hospital from 10 pregnant women 7 people (70%) of whom experienced sleep disorders and 3 people (30%) did not experience, 6 people (60%) of 10 mothers who experienced sleep disorders on average because of a lot of activity. The purpose of the study was to determine the relationship between anxiety and physical activity with sleep disturbances in TM III pregnant women at Ummi Hospital, Bengkulu City. The method used with a cross sectional design, the sample in this study was rounded up to 79 sampling techniques in this study were accidental sampling. data analysis using Chi Square. Univariate analysis results that most of the pregnant women TM III 48 (60.8%) who experienced mild anxiety, most of the pregnant women TM III 46 (58.2%) who had mild physical activity and most of the respondents 42 (53.2%) who had less sleep at Ummi Hospital Bengkulu in 2024. Meanwhile, Bivariate analysis shows that there is a correlation between anxiety and physical activity with sleep disorders at Ummi Hospital Bengkulu in 2024 with a P-value of 0.000. It can be concluded that this study becomes valuable input for pregnant women to know about the importance of reducing anxiety to achieve the expected quantity of sleep so that they can relax and not to experience sleep disturbances. It is also important that being better prepared when later experiencing anxiety or sleep disturbances